2011
DOI: 10.5539/jedp.v1n1p154
|View full text |Cite
|
Sign up to set email alerts
|

Non-formal Education Programmes and Poverty Reduction among Young Adults in Southern Senatorial District, Cross River State, Nigeria

Abstract: The study investigated the influence of non-formal education programmes on poverty reduction among young adults in southern senatorial district of Cross River State, Nigeria between 2000-2005. Three hypotheses were postulated and tested. Data were collected using the Poverty Reduction Inventory (PRI). The stratified random sampling technique was used based on location (Local Councils and existing political wards) to select four local government areas and forty local wards. From these local government areas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Although beneficiaries gained some livelihood skills and life skills, these skills were not transferable in the labour market in order to improve the lives of poor people (Morton & Montgomery, 2011). Akpama et al (2011) evaluated NFET programmes linked to poverty reduction among adults in the Southern Senatorial District, Cross River State, Nigeria. The authors investigated the extent to which these NFET programmes had contributed to the reduction of poverty among the youth and adults in their respective study areas (Akpama et al, 2011).…”
Section: Conceptual Framework and Approach Of Nfet In South Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Although beneficiaries gained some livelihood skills and life skills, these skills were not transferable in the labour market in order to improve the lives of poor people (Morton & Montgomery, 2011). Akpama et al (2011) evaluated NFET programmes linked to poverty reduction among adults in the Southern Senatorial District, Cross River State, Nigeria. The authors investigated the extent to which these NFET programmes had contributed to the reduction of poverty among the youth and adults in their respective study areas (Akpama et al, 2011).…”
Section: Conceptual Framework and Approach Of Nfet In South Africamentioning
confidence: 99%
“…Akpama et al (2011) evaluated NFET programmes linked to poverty reduction among adults in the Southern Senatorial District, Cross River State, Nigeria. The authors investigated the extent to which these NFET programmes had contributed to the reduction of poverty among the youth and adults in their respective study areas (Akpama et al, 2011). The findings reveal that skills acquisition did not significantly influence poverty reduction among the young and adults (Akpama et al, 2011).…”
Section: Conceptual Framework and Approach Of Nfet In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Md Rezaul Islam et al (2012) and Marit Blaak et al (2012) examined the relevance of NFET for income generation. Matthew Morton and Paul Montgomery (2011) and Simon Ibor Akpama et al (2011) studied its impact on socio-economic empowerment and reducing adult poverty. Despite such research exploring the relationship between NFET programmes and employment, little is known about the extent to which the material and human resources of NFET centres enable or disable graduates' wageor self-employment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has addressed several aspects of NFET, including the examination of the relevance of NFET for income generation (Islam et al 2012;Blaak et al 2012); acquisition of practical skills (Georgiadou et al 2009;Islam et al 2012); socioeconomic empowerment of adults who are poor (Morton and Montgomery 2011;Akpama et al 2011); the ineffectiveness of NFET; and skills mismatch in terms of supply and demand on the labour market (Morton and Montgomery 2011;Anderson 2012). Research has shown that NFET centres and their adult trainees continue to experience challenges due to the insufficiency of enabling environments (DHET 2012;Aitchison 2007;Blaak et al 2012).…”
Section: Introductionmentioning
confidence: 99%